Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Equation P: a + b = 6
Equation Q: 4a + 2b = 19

Which of the following steps can be used to eliminate the a term?

−1(4a + 2b = 19)
−4(4a + 2b = 19)
−4(a + b = 6)
4(a + b = 6)


Sagot :

Answer:

-4(a + b = 6)

Step-by-step explanation:

When you multiply equation P by -4, you obtain -4a - 4b = -24. You can then add this equation to equation Q to eliminate the a term.

We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.